Enhancing digital video analysis of bar kinematics in weightlifting: A case study - Daehlin, T. E.; Krosshaug, T.; Chiu, L. Z. F. (The Journal of Strength and Conditioning Research, 2017)
Weightlifting technique can be objectively assessed from two-dimensional video recordings. Despite its importance, participants' bar trajectories in research involving the snatch or clean exercises are often not reported, potentially due to the time required to digitize video. The purpose of this investigation was to evaluate the use of a light-emitting diode (LED)-based marker, digital video, and open-source software to automatically track the bar end during weightlifting exercises. A former national-level weightlifter was recorded with a digital video camera performing the snatch, clean and jerk, and squat exercises. An LED-based marker was placed on the right end of the bar. This marker was automatically tracked using 2 open-source software programs to obtain vertical and horizontal position coordinates. The LED-based marker was successfully auto-tracked for all videos over a variety of camera settings. Furthermore, the vertical and horizontal bar displacements and vertical bar velocity were consistent between the 2 software programs. This study demonstrates that an LED-based marker can be automatically tracked using open-source software. This combination of an LED-based marker, consumer camera, and open-source software is an accessible, low-cost method to objectively evaluate weightlifting technique.